Weighting of Prosodic and Lexical-Semantic Cues for Emotion Identification in Spectrally Degraded Speech and With Cochlear Implants. Issue 6 (November 2021) - Richter, Margaret E.; Chatterjee, Monita
Abstract : Objectives: Normally-hearing (NH) listeners rely more on prosodic cues than on lexical-semantic cues for emotion perception in speech. In everyday spoken communication, the ability to decipher conflicting information between prosodic and lexical-semantic cues to emotion can be important: for example, in identifying sarcasm or irony. Speech degradation in cochlear implants (CIs) can be sufficiently overcome to identify lexical-semantic cues, but the distortion of voice pitch cues makes it particularly challenging to hear prosody with CIs. The purpose of this study was to examine changes in relative reliance on prosodic and lexical-semantic cues in NH adults listening to spectrally degraded speech and adult CI users. We hypothesized that, compared with NH counterparts, CI users would show increased reliance on lexical-semantic cues and reduced reliance on prosodic cues for emotion perception. We predicted that NH listeners would show a similar pattern when listening to CI-simulated versions of emotional speech. Design: Sixteen NH adults and 8 postlingually deafened adult CI users participated in the study. Sentences were created to convey five lexical-semantic emotions (angry, happy, neutral, sad, and scared), with five sentences expressing each category of emotion. Each of these 25 sentences was then recorded with the 5 (angry, happy, neutral, sad, and scared) prosodic emotions by 2 adult female talkers. The resulting stimulus set included 125 recordings (25 Sentences × 5 Prosodic Emotions) per talker, of which 25 were congruent (consistent lexical-semantic and prosodic cues to emotion) and the remaining 100 were incongruent (conflicting lexical-semantic and prosodic cues to emotion). The recordings were processed to have 3 levels of spectral degradation: full-spectrum, CI-simulated (noise-vocoded) to have 8 channels and 16 channels of spectral information, respectively. Twenty-five recordings (one sentence per lexical-semantic emotion recorded in all five prosodies) were used for a practice run in the full-spectrum condition. The remaining 100 recordings were used as test stimuli. For each talker and condition of spectral degradation, listeners indicated the emotion associated with each recording in a single-interval, five-alternative forced-choice task. The responses were scored as proportion correct, where "correct" responses corresponded to the lexical-semantic emotion. CI users heard only the full-spectrum condition. Results: The results showed a significant interaction between hearing status (NH, CI) and congruency in identifying the lexical-semantic emotion associated with the stimuli. This interaction was as predicted, that is, CI users showed increased reliance on lexical-semantic cues in the incongruent conditions, while NH listeners showed increased reliance on the prosodic cues in the incongruent conditions. As predicted, NH listeners showed increased reliance on lexical-semantic cues to emotion when the stimuli were spectrally degraded. Conclusions: The present study confirmed previous findings of prosodic dominance for emotion perception by NH listeners in the full-spectrum condition. Further, novel findings with CI patients and NH listeners in the CI-simulated conditions showed reduced reliance on prosodic cues and increased reliance on lexical-semantic cues to emotion. These results have implications for CI listeners' ability to perceive conflicts between prosodic and lexical-semantic cues, with repercussions for their identification of sarcasm and humor. Understanding instances of sarcasm or humor can impact a person's ability to develop relationships, follow conversation, understand vocal emotion and intended message of a speaker, following jokes, and everyday communication in general. Abstract : Supplemental Digital Content is available in the text.